Strong Electronic Interaction of Amorphous Fe2O3 Nanosheets with Single‐Atom Pt toward Enhanced Carbon Monoxide Oxidation. (15th August 2019) - Chen, Wenlong; Ma, Yanling; Li, Fan; Pan, Lei; Gao, Wenpei; Xiang, Qian; Shang, Wen; Song, Chengyi; Tao, Peng; Zhu, Hong; Pan, Xiaoqing; Deng, Tao; et al.
Abstract: Platinum‐based catalysts are critical to several chemical processes, but their efficiency is not satisfying enough in some cases, because only the surface active‐site atoms participate in the reaction. Henceforth, catalysts with single‐atom dispersions are highly desirable to maximize their mass efficiency, but fabricating these structures using a controllable method is still challenging. Most previous studies have focused on crystalline materials. However, amorphous materials may have enhanced performance due to their distorted and isotropic nature with numerous defects. Here reported is the facile synthesis of an atomically dispersed catalyst that consists of single Pt atoms and amorphous Fe2 O3 nanosheets. Rational control can regulate the morphology from single atom clusters to sub‐nanoparticles. Density functional theory calculations show the synergistic effect resulted from the strong binding and stabilization of single Pt atoms with the strong metal‐support interaction between the in situ locally anchored Pt atoms and Fe2 O3 lead to a weak CO adsorption. Moreover, the distorted amorphous Fe2 O3 with O vacancies is beneficial for the activation of O2, which further facilitates CO oxidation on nearby Pt sites or interface sites between Pt and Fe2 O3, resulting in the extremely high performance for CO oxidation of the atomic catalyst. Abstract : An atomically Pt dispersed catalyst on amorphous Fe2 O3 nanosheets is developed. The size effect of Pt and phase effect of support are explored. The synergistic effect results from the strong metal‐support interactions between the single Pt atoms and the amorphous Fe2 O3 structure supports lead to an enhanced CO oxidation performance.